Access price regulation and price discrimination in intermediate goods markets - Claudia Salim (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
We consider a model of a monopolistic network operator who sequentially offers two-parted access charges to symmetric downstream firms. We are particularly interested in analyzing an alternative to current regulatory practice of prescribing access. In particular, we look at the possibility of restraining the input monopolist's market power by endowing downstream firms with a regulatory option: In case they disagree with the contracts proposed to them, downstream firms can claim a regulated access price. It turns out that this form of regulation may prevent foreclosure even though allowing for price discrimination in the intermediary market. It proves itself more beneficial to welfare than the current practice of prescribing access prices above marginal cost. Interestingly, even though one expects discrimination against the first mover, non-discriminatory input prices below cost can occur when the monopolist faces the alternative of a rather strictly cost-oriented regulated access price. Non-discrimination rules will either not become effective or result in less optimal price levels.
Keywords: D43; L13; L14; L42; 330; price discrimination; vertical contracting; exclusion; regulatory outside option; Netzzugang; Lieferanten-Kunden-Beziehung; Preisdifferenzierung; Vertragstheorie; Staatliche Preispolitik; Theorie